Perancangan Media Pembelajaran Fisika Materi Konsep Termodinamika Dalam Mesin Kalor Dan Sifat-Sifat Gas Ideal Monoatomik Untuk SMA Kelas XI IPA - Sitohang, Hotmian (STMIK Palangkaraya, 2016)
Computer-based learning system is now much improved, making the faculty more enthusiastic in making a model of learning so that students do not get bored easily. Physics is a subject that is grealty feared by students because the course is filled by counting, concepts and formulas. designing or creating instructional media. Learning physics is expected to be an interactive learning tool that can improve the learning interest of the user. This study uses R & D (Research and Development), namely the development of computer-based animation instructional media. Making learning applications of thermodynamics in physics to the concept of heat engines and properties of monatomic ideal gas is by using Visual Basic 6.0 software to design the application, Microsoft Access 2007 to design a database system for data storage applications, while Adobe Photoshop to design the image. The test results showed that the instructional media program for the display program, the suitability of the program with the teaching material, and technical quality were good. Based on these results it can be concluded that the program deserves to be a medium of learning and can be used in teaching Physics especially about heat engines and thermodynamic properties of monatomic ideal gas to high school grade XI.